Drain tip culture following total knee arthroplasty - Aski, Bahubali; Vaidya, Narendra; Patil, Rakesh; Pinto, Nelson (International Journal of Research in Medical Sciences, 2017)
Background: Placing a suction drain following total knee replacement is usual practice which is been followed by many surgeons. Closed suction drainage following arthroplasty is a routine with the aim of preventing wound hematoma and thereby reducing the risk of infection. Surgical site infections (SSI) in orthopaedic surgeries are disastrous and often lead to significant morbidity and mortality. Usefulness of drain tip culture in predicting the wound infection is been tested but results are controversial. Methods: It is a prospective study of 546 drains (352 patients) who underwent unilateral or bilateral Total Knee Arthroplasty (TKA). The drain tip was sent for culture at the time of removal. Cultures from the SSI were also collected. Cases that had at least six months of follow up were included in the study. Results: Drain tip culture was positive in total of 18 patients. Three patients had developed deep infection and 10 patients had superficial infection. All three patients with deep infection and 9 out of 10 patients of superficial infection were drain tip culture positive. Out of 9 culture positive superficial infections, one had different bacteria identified from the wound site. Drain tip culture was positive in 3.39% of drains and infection (wound culture) was positive in 2.26% of wounds. On statistical analysis we found drain tip culture has sensitivity of 91.66%, specificity of 98.64%, positive predictive value of 61.11% and negative predictive value of 99.8%. Conclusion: Drain tip culture positivity helps in predicting the future chance of developing the infection. If drain tip culture is negative, then there is almost near nil chances of infection.